Kepemimpinan Kepala Sekolah Dalam Rangka Meningkatkan Kualitas Mutu Di SDN Lidah Wetan IV - Isnayni Firdayanti; Tiara Agil Salsabila; Shinta Salsabila; Nibras Khansa N.; Cantik Oktaviana E.; Dwi Oktavia; Halimatus Sakdiyah (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2023)
The purpose of the research in this discussion is to find out and analyze from the start the roles and tasks as the leader of the course of education or known as the principal of an elementary school. Leadership is an ability that every person needs to have to be able to influence others in helping the path of goals so that they can be achieved and can run according to plan and the goals are right on what is intended. The notion of leadership is someone who wants to be recognized as a leader by having advantages in several functions including the advantages of being able to influence, guide, manage other people, and evaluate all activities up to human resources, besides the advantages of a leader must have a ready mentality, one of which is a leader in the world of education which can be interpreted as the principal has the task of being able to be a driver, guide, direct, and move other people who have a relationship with the implementation and development of education and teaching, so that activities can run effectively and efficiently in achieving the vision and mission of an education. the principal as a superior needs to pay attention to subordinates to be able to support a series of educational activities, the achievement of quality education as a point of understanding that needs to be considered as a school principal in driving the course of education is an organic system where schools are one of them, smoothness and prosperity built by the principal later it will provide high quality value for an educational institution he leads where all the goals that are expected together can be achieved and all human resource needs in carrying out their duties are properly fulfilled.